DEKONSTRUKSI FILSAFAT CINTA RABI’AH AL-ADAWIYYAH DALAM PERSPEKTIF JACQUES DERRIDA - Usmi laila; Ismail Ismail; Rahmat Ramdhani (Sekolah Pasca Sarjana IAIN Bengkulu, 2023)
Abstract: This research was motivated by the author's doubts about the texts of Rabi'ah al-Adawiyyah's philosophy of love. With the purpose of the study, namely Describing the meaning of love Rabi'ah al-Adawiyyah. Describe and analyze the form of Rabi'ah al-Adawiyyah's love texts. Examine, analyze, and interpret the deconstruction of Rabi'ah al-Adawiyyah's philosophy of love in his love conversation texts from the perspective of Jacques Derrida's Hermeneutics. In theory, using the deconstruction of Jacques Derrida, deconstruction dismantles established texts, giving rise to hidden meanings behind them. This research uses library research methods and philosophical research approaches. The results showed that the meaning of Rabi'ah love is mahabbah, divided into two concepts, namely longing love and love because God deserves to be loved. The Rabi'ah love script is in the form of poetry poems that mean deep love. The deconstruction of Rabi'ah al-Adawiyyah's philosophy of love is characterized by binary opposition, logocentrism and difference Derrida is his apathy and skepticism towards God's creatures, then makes himself not put love trust in humans, so that only God makes himself feel existing. Rabi'ah's path of mahabbah is bridged by his inability to face the world.Keywords: Deconstruction, Philosophy of Love, Rabi'ah Al-Adawiyyah. Abstrak: Penelitian ini dilatarbelakangi oleh keraguan-keraguan penulis terhadap teks-teks naskah filsafat cinta Rabi’ah al-Adawiyyah. Dengan tujuan penelitian yaitu Mendeskripsikan makna cinta Rabi’ah al-Adawiyyah. Mendeskripsikan dan menganalisa bentuk naskah-naskah cinta Rabi’ah al-Adawiyyah. Menelaah, menganalisa, dan memaknai dekonstruksi filsafat cinta Rabi’ah al-Adawiyyah dalam teks-teks percakapan cintanya perspektif Hermeneutika Jacques Derrida. Secara teori menggunakan dekonstruksi Jacques Derrida, dekonstruksi membongkar teks yang sudah mapan sehingga memunculkan makna tersembunyi dibalik teks. Penelitian ini menggunakan metode library research (penelitian kepustakaan) dan pendekatan penelitian filosofis. Hasil penelitian menunjukkan bahwa makna cinta Rabi’ah adalah mahabbah, dibagi dalam dua konsep yakni cinta rindu dan cinta karena Tuhan memang layak untuk dicintai. Adapun naskah cinta Rabi’ah adalah berbentuk syair-syair sajak puisi yang bermakna cinta mendalam. Dekonstruksi dari filsafat cinta Rabi’ah al-Adawiyyah ditandai dengan oposisi biner, logosentrisme dan difference Derrida adalah sikapnya yang apatis dan skeptis terhadap makhluk ciptaan Tuhan, kemudian menjadikan dirinya tidak menaruh kepercayaan cinta kepada manusia, sehingga hanya Tuhanlah yang membuat dirinya merasa ada. Jalan mahabbah Rabi’ah yakni dijembatani oleh ketidakmampuannya dalam menghadapi dunia. Kata Kunci : Dekonstruksi, Filsafat Cinta, Rabi’ah Al-Adawiyyah.